CRISPR/Cas9-mediated generation of AP-1 activity reporter cell line in human embryonic stem cell (WAe007-A-5) - Xingyou Guo; Meng Zhang; Zhanglei Xu; You Yu; Zhenya Shen (Stem Cell Research)
Activator protein 1 (AP-1) is involved in cell fate determination and function. To monitor the AP-1 activity, we cloned a AP-1 binding sites fragment into the upstream of minimal TATA-box promoter, then a luciferase-GFP reporter (LuciGFP) was designated to the downstream of the promoter. With CRISPR/Cas9, the AP-1-LuciGFP reporter was introduced into AAVS1 locus, a safe harbor for gene editing. Thus, this AP-1-LuciGFP reporter cell line could be subjected to monitor the AP-1 activity during the cell differentiation, cell fate transition and disease modeling.